Organizational Basics of Special and PreCompetition Preparation Stages for Athletes - Kholmirzayev Ernazar Jurayevich (Euro Asian Journal Publishing, 2023)
This article focuses on the factors affecting the psychological state of athletes by using micro-cyclists during the special and competitive stages of the military service.
Keywords: exercise; sports; competitions